(untitled) (Research, Society and Development, 2020)
The number of domestic animals that are being inserted into families and society as members of them is increasing, and together with this approach there is an increase in concern and care for these animals. Thus, the present work was carried out with the main objective of assessing the level of knowledge of the students of the Full Degree in Biology course at the Federal University of Piaui, Campus of Picos-PI, related to the well-being of pets (dogs and cats). For that, forms with closed questions were used as research tool, which were applied randomly to a sample of 200 students from the Biology course at UFPI, Campus of Picos-PI. For the results, data for p ≤ 0.05 were considered significant. It was found about animal welfare, that the majority of respondents (75%) had correct knowledge regarding the set of practices related to such; regarding responsible custody, 34% stated that it is taking care of the animal’s physical and mental health by not mistreating and offering them affection; about mistreatment, students have a good knowledge: 94% of the sample was affirmative in the crime that such activities represent. In view of the results, there was satisfactory the level of knowledge on the subject, however the implementation of ways for the dissemination of information encompassing all members of society must be mandatory in order for maintenance and improvement in the coexistence of humans with the animals.